Viúvas de Gangues: o universo interdito da violência urbana juvenil - Marinho, Camila Holanda (2004)
The central theme of this study is to understand how to live and construct meaning about life experiences of a group of young urban poor in Fortaleza involved in everyday situations marked by violence. From this scenario intitulo as young widows , girls who live in these locations that were related and had children with boys who died their involvement in violent situations . Seek to achieve in their speeches and in their representations understandings they have about motherhood , death , female behavior and social spaces where they live in order to reveal the production of the symbolic universe that attach social life . To use it as a methodological resource narrate their life trajectories to locate them as producers of representations previously said . The intention is to weave a cultural analysis of the behavior of the group of young widows from the perspective of Clifford Geertz , where culture is understood as a system of " signs interpretable " , a "web of meanings " that articulate the action of men in society , and for this it is necessary ethnography , noting the social discourses to achieve these meanings.